2017
DOI: 10.3233/jad-170308
|View full text |Cite
|
Sign up to set email alerts
|

Association of Radon Background and Total Background Ionizing Radiation with Alzheimer’s Disease Deaths in U.S. States

Abstract: Our findings, like other studies, suggest that ionizing radiation is a risk factor for AD. Intranasal inhalation of radon gas could subject the rhinencephalon and hippocampus to damaging radiation that initiates AD. The damage would accumulate over time, causing age to be a powerful risk factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Plus, Radon and its daughters may also pass the blood -brain -barrier. Damage would accumulate over time making also age to be a powerful risk factor 32 . Other cohort studies evaluated health outcome medical workers exposed to IR 11,33-36 but to our knowledge none of them focused on its impact on the brain.…”
Section: Clinical Effects Of Low Dose Exposition On the Brainmentioning
confidence: 99%
“…Plus, Radon and its daughters may also pass the blood -brain -barrier. Damage would accumulate over time making also age to be a powerful risk factor 32 . Other cohort studies evaluated health outcome medical workers exposed to IR 11,33-36 but to our knowledge none of them focused on its impact on the brain.…”
Section: Clinical Effects Of Low Dose Exposition On the Brainmentioning
confidence: 99%
“…However, the authors recommend continuing the health supervision of this population (from HBRA) in the future [27,28]. Lehrer, S. et al, 2017 found the strong correlation between natural background radiation and risk of developing Alzheimer Disease [29]. Still, this question is under discussion, as there are might be ecological fallacy.…”
mentioning
confidence: 98%
“…The other 19 papers recommended conducting long-term research. Only in one paper was found neurological disorder, such as Alzheimer's disease (AD) [29].According to the United Nations Scientific Committee on the Effects of Atomic Radiation (UNSCEAR), there are four main sources, which form the Natural Background Radiation: cosmic rays, terrestrial radiation, intakes of naturally occurring radionuclides through inhalation and ingestion.…”
mentioning
confidence: 99%
“…Injury to the brain from trauma or irradiation may initiate the process [3]. The characteristic pathologic plaques and tangles are a non-specific result of the disease process, not a cause [4].…”
mentioning
confidence: 99%